Organizational Performance in Higher Education: How Transformational Leadership and Innovation Policy Influence - Putra, Riki Wanda; Susanto, Perengki; Rasyid, Rosyeni (Yayasan Sinergi Kawula Muda, 2025)
The purpose of this research is to see the effect of transformational leadership and innovation policy on organizational performance. This research is a combine between quantitative method and an associative approach. The research instrument is a questionnaire given to 40 samples. Data analysis techniques using multiple linear analysis with the help of SPSS applications. The normality test used is the Kolmogorov-Smirnov test with a significance value of 0.20. The results of the linearity test between Transformational Leadership (X1) on Organizational Performance (Y) with an F-count value of 18.83, in other words it can be concluded that there is a linear relationship between Transformational Leadership (X1) on Organizational Performance (Y). Furthermore, it is concluded that there is a linear relationship between Innovation Policy (X2) on Organizational Performance (Y) with an F-count value of 11.20. Then the multicollinearity value is obtained from the count of 4.630 and 3.443, in other words it can be concluded that there is no between the independent variables, namely Transformational Leadership (X1) with Innovation Policy (X2) in relation to the dependent variable Organizational Performance (Y). The results showed that there is a positive influence of transformational leadership and innovation policy on organizational performance. This research suggests developing programs that support innovation policies and improving transformational leadership in organizations to strengthen overall performance. In addition, other recommendations include the implementation of training programs for leaders to hone their transformational leadership skills, as well as the development of more effective innovation policies to create a work environment that encourages creativity and adaptability.